INTERAKSI SOSIAL JAMAAH TABLIGH DI KOTA MALANG (Studi tentang Interaksi Sosial Jamaah Tabligh di Masjid Pelma dan Ponpes Jami'urrahman Malang) - Haris Mahdi (lp2m-uin malang, 2007)
This study will discuss the understanding and matters pertaining to meaning of culture-value orientation, the typology of social action/interaction and the tendency of social action/interaction of the member of Jamaah Tabligh, in organizational context both internally and externally. The approach of this research is survey-descriptive approach with individual analysis unit. The collection of samples is using sampling quota of 103 respondents. The data collection is using triangulation model. This research describes that in the perspective of culture-value orientation there are basic values of Jamaah Tabligh about five basic human issue, i.e.: the essence of life, the essence of work, perception of time, view about nature, and human interrelationship. In their daily activities, the members of Jamaah Tabligh tend to be rational with value oriented. In the matter of organizational internals, the social interaction developed by Jamaah Tabligh is associative-cooperative. If an internal conflict happen, the accommodation form that is built including toleration or tolerant participation, compromise, arbitration, and mediation. The social interaction of Jamaah Tabligh with outside party is the mixture of associative-cooperative and associative-accommodation. The associative-cooperative side is visible in members’ daily lives, who also actively involved in society’s activities. The form of accommodation in the context of social interaction of Jamaah Tabligh with other parties is by trying to compromise by explaining the religious mission done by Jamaah Tabligh. If it is failed, Jamaah Tabligh does the toleration. Keyword: Social Interaction, Jamaah Tabligh